Power Amplification Efficient Transmitter Structures for Massive MIMO with SC-FDE Schemes: A Promising Combination for 5G Systems? - Montezuma, Paulo; Ferreira, Afonso; Dinis, Rui; Beko, Marko (Společnost pro radioelektronické inženýrství, 2018)
It is well-known that massive multiple-input multiple-output (MIMO) systems have high potential for future wireless broadband systems. Requirements such as high spectral and power efficiency are also crucial in 5G. Based on a multi-amplifier structure it is possible to define a double layered structure where each amplification branch is connected to an antenna array to achieve both constellation and power directivies, assuring at same time similar performances to systems using transmitters with 2-dimensional antenna arrays. Thus, a different path can be followed to improve energy efficiency of power amplification where the usage of parallel amplification branches is combined with big arrays of antennas and multi-stream communication systems. These systems can be combined with single-carrier with frequency domain equalization (SC-FDE) schemes to improve the power efficiency in uplink due to the low envelope fluctuations.
Keywords: massive MIMO; multi-amplifier; power efficiency; double layered structure